Performance and mechanisms of enhanced hydrolysis acidification by adding different iron scraps: Microbial characteristics and fate of iron scraps - Wang, Yanqiong; Wang, Hongwu; Jin, Hui; Chen, Hongbin (Frontiers in Microbiology, 2022)
HA, as one of low-carbon pretreatment technology could be enhanced by packing of iron or iron oxide powder for enhancing the transformation of large molecular weight to generate volatile fatty acids (VFAs) for fuel production. However, the controversy of iron strengthening the HA and inherent drawbacks of iron oxide, such as poor mass transfer, and difficult recovery, limit this pretreatment technology. Clean and rusty iron scraps were packed into an HA system to address these issues while focusing on the system performance and the response of core bacterial and fungal microbiomes to iron scrap exposure. Results showed that clean and rusty iron scraps can significantly improve the HA performance while considering hydrolysis efficiency (HE), acidification efficiency (AE) and VFAs production, given that VFAs ratios (Cacetate: Cpropionate: Cbutyrate) were changed from the 14:5:1 to 14:2:1 and 29:4:1, respectively and the obtained VFA ratios in iron scraps addition systems were more closely to the optimal VFAs ratio for lipids production. Redundant and molecular ecological network analyses indicated that iron scraps promote the system stability and acidogenesis capacity by boosting the complexity of microbes’ networks and enriching core functional microbes that show a positive response to HA performance, among which the relative abundance of related bacterial genera was promoted by 19.71% and 17.25% for RRusty and RClean systems. Moreover, except for the differences between the control and iron scraps addition systems, the findings confirmed that the RRusty system is slightly different from the RClean one, which was perhaps driven by the behavior of 6.20% of DIRB in RRusty system and only 1.16% of homoacetogens in RClean system when considering the microbial community and fate of iron scraps. Totally, the observed results highlight the application potential of the iron scrap-coupled HA process for the generation of VFAs and provide new insights into the response of different iron scraps in microbes communities.